The classification of the southern and south-tropical African Kalanchoe [subg. Kalanchoe] sect. Raveta (Crassulaceae subfam. Cotyledonoideae) expanded and refined: description of K. [sect. Raveta] ser. Paniculatae, K. [sect. Raveta] ser. Alticolae, K. [sect. Raveta] ser. Leblanciae, K. [sect. Raveta] ser. Humiles, and K. [sect. Raveta] ser. Elizae - Smith, Gideon F. (Phytotaxa, 2025)
Five new series, i.e., [1.] K. ser. Leblanciae, [2.] K. ser. Alticolae, [3.] Kalanchoe ser. Paniculatae, [4.] K. ser. Humiles, and [5.] K. ser. Elizae, are described in K. [subg. Kalanchoe] sect. Raveta. The type species of all five series are indigenous to southern and / or south-tropical Africa. The first new series, K. ser. Leblanciae, includes only K. leblanciae, which is a tall-growing, climbing to leaning shrub or shrublet with small, yellow flowers. The second new series, K. ser. Alticolae, includes small shrublets with yellow or reddish orange flowers generally with prominent sepals. The third new series, K. ser. Paniculatae, includes the robust, large- and petiolate-leaved, non-waxy kalanchoes with large, yellow flowers borne on tall inflorescences. The fourth new series, K. ser. Humiles, includes small-growing plants with variously purplish-mottled leaves and very small, purplish flowers. The fifth and final new series, K. ser. Elizae, includes species with large, generally sessile leaves and large, yellow or white flowers. The species included in K. ser. Alticolae were previously included in K. [subg. Kalanchoe sect. Raveta] ser. Rotundifoliae, and K. leblanciae was previously included in K. [subg. Kalanchoe sect. Raveta] ser. Longiflorae. Description of K. ser. Alticolae and K. ser. Leblanciae therefore necessitates amendment of the descriptions of K. ser. Rotundifoliae and K. ser. Longiflorae, respectively, also because the red-flowered K. crundallii is here included in K. ser. Longiflorae. Kalanchoe ser. Rotundifoliae is here excluded from K. [subg. Kalanchoe] sect. Raveta. At the rank of series, the species included in K. ser. Paniculatae, K. ser. Humiles, and K. ser. Elizae were previously unplaced.